The Role of The Governor as a Representative of The Central Government in Managing Mandatory Government Affairs of Basic Services in The Field of Security, Public Order and Public Protection in Central Sulawesi Province - Dadang Supriatna; Arief Mulia Edi; Florianus Aser (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study aims to analyze the role of the Governor as the Representative of the Central Government (GWPP) in managing mandatory governmental affairs related to public peace, public order, and community protection (Trantibumlinmas) in Central Sulawesi Province. The study is motivated by the increasing number of public order disturbances, low disaster mitigation capacity, weak population administration services, and significant regional development disparities in Central Sulawesi. This research employed a descriptive method with a qualitative approach. Data were collected through interviews, observations, documentation studies, and literature reviews involving the Civil Service Police Unit (Satpol PP), Regional Disaster Management Agency (BPBD), Population and Civil Registration Office (Dukcapil), and the Regional Secretariat of Central Sulawesi Province. Data analysis was conducted using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The findings indicate that the Governor’s role as GWPP has been implemented through guidance, supervision, coordination, and facilitation functions in accordance with Law Number 23 of 2014 and Government Regulation Number 33 of 2018. However, its implementation has not yet been optimal due to budget limitations, extensive and archipelagic geographical conditions, sectoral ego among regions, and the complexity of social conflicts and disasters. This study also proposes an ideal model for sustainable Trantibumlinmas management through the “3-Layer GWPP Pyramid Model,” which emphasizes a risk-based preventive approach, integrated command-based coordination, and supervision based on minimum service standards supported by an integrated digital system. This model is expected to strengthen human security, improve governance effectiveness, and create adaptive, responsive, and sustainable public services in Central Sulawesi Province.